9514 1404 393
Answer:
b. g(x) = 0.5f(x)
Step-by-step explanation:
Compared to the line y=x, the graph of g(x) has a vertical scale factor of 1/2. We can also observe that the equation for g(x) is ...
g(x) = 1/2x
If we substitute f(x) for x, then this is ...
g(x) = 1/2f(x) . . . . matches choice B
Answer:
![x = \frac{5}{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B5%7D%7B4%7D)
Step-by-step explanation:
![\frac{2x-1}{3} = \frac{1}{2} \\](https://tex.z-dn.net/?f=%5Cfrac%7B2x-1%7D%7B3%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5C%5C)
Here cross - multiplying 3 & 2 gives :-
![2(2x-1) = 3](https://tex.z-dn.net/?f=2%282x-1%29%20%3D%203)
Solving this further gives :-
![2(2x-1) = 3\\=> 4x-2 = 3\\=>4x = 3+2\\=> 4x=5\\=> x = \frac{5}{4}](https://tex.z-dn.net/?f=2%282x-1%29%20%3D%203%5C%5C%3D%3E%204x-2%20%3D%203%5C%5C%3D%3E4x%20%3D%203%2B2%5C%5C%3D%3E%204x%3D5%5C%5C%3D%3E%20x%20%3D%20%5Cfrac%7B5%7D%7B4%7D)
Answer:
Step-by-step explanation:
1. Y varies jointly as R and T
Y = k*R*T
Y = kRT
Where,
k = constant of proportionality
2. B is directly proportional to the square of A and inversely proportional to the cube of C.
B = k(A²) / C³
B = kA²/C³
Where,
k = constant of proportionality